Molecular phylogeny and character evolution of Anemiaceae (Schizaeales). Issue 6 (11th December 2018) - Labiak, Paulo H.; Mickel, John T.; Hanks, Judith G.
Abstract: Anemiaceae is one of the most ancient extant fern families, with fossils known since the Jurassic. Nowadays it has about 115 species, distributed in the Neotropics, Africa, Madagascar, and India. We analyzed the relationships among 81 species of Anemiaceae, based on four cpDNA regions, rbcL, rps4-trnS, trnG-trnR, and trnL-trnF . This sampling corresponds to approximately 70% of the family diversity, includes taxa from the main biogeographic areas, and represents all of the genera, subgenera and sections traditionally recognized in the family. Our results support the monophyly of Anemiaceae, and the recognition of a single genus, Anemia, which can be further subdivided in three subgroups: subg. Anemia, subg. Anemiorrhiza and the Mohria clade. In general, most of the sections that are recognized in Anemia are supported as natural groups, but some of them will need to have their circumscriptions altered in order to preserve monophyly. We also explored the evolution of morphological characters by optimizing them on the phylogenetic tree. Our results show that characters that have been traditionally used in the taxonomy of both extant and ancient groups, such as leaf dimorphism, and perispore morphology, are homoplastic within Anemiaceae.